2007
DOI: 10.1088/1464-4258/9/6/s09
|View full text |Cite
|
Sign up to set email alerts
|

Optical fibre grating refractometers for resin cure monitoring

Abstract: Integrated Optical Fibre (IOF) is a passive optical platform that directly integrates optical fibre to a planar substrate, illustrated in Fig 1(a). It possess advantages associated with optical fibre such a low propagation loss, whilst enabling planar functionality commonplace with integrated optics. Planarization is uniquely achieved through a modified Flame Hydrolysis Deposition (FHD) technique that forms a robust glass alloy between the fibre and substrate. The binding medium is of optical quality and resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…A multi-point flow detection system comprised of consecutive bare and grated regions along a single fiber was developed and experimentally validated; resin arrival was successfully detected on all bare regions. Buggy et al [46] employed two Fresnel OFRs operating in different wavelengths to monitor the curing of an epoxy resin. The measured refractive index increased rapidly after an initial decrease, indicating correlation with viscosity.…”
Section: Sensors Detecting Optical Properties 231 Optical Fiber Rementioning
confidence: 99%
“…A multi-point flow detection system comprised of consecutive bare and grated regions along a single fiber was developed and experimentally validated; resin arrival was successfully detected on all bare regions. Buggy et al [46] employed two Fresnel OFRs operating in different wavelengths to monitor the curing of an epoxy resin. The measured refractive index increased rapidly after an initial decrease, indicating correlation with viscosity.…”
Section: Sensors Detecting Optical Properties 231 Optical Fiber Rementioning
confidence: 99%
“…When the curvature was within the range of 0-2 m −1 , the resonance amplitude depth increased linearly and the position of the resonance wavelength remained unchanged, at a sensitivity of 5.065 dBm −1 . In 2007, Buggy et al (9) monitored variations in refractive index during resin curing by employing three fiber optic sensors, namely the LPFG, tilted Bragg gratings, and the Fresnel refractometer. Their results revealed that the refractive indices measured using the LPFG and the Fresnel refractometer were highly consistent.…”
Section: Introductionmentioning
confidence: 99%
“…As the coupling wavelength and efficiencies are dependent upon the properties of the cladding modes, the resonance features in the TFBG transmission spectrum exhibit sensitivity to surrounding refractive index [10,11]. Analysis of the transmission spectrum facilitates measurements with resolution of 10 -4 RIU [11].…”
Section: Introductionmentioning
confidence: 99%
“…As the coupling wavelength and efficiencies are dependent upon the properties of the cladding modes, the resonance features in the TFBG transmission spectrum exhibit sensitivity to surrounding refractive index [10,11]. Analysis of the transmission spectrum facilitates measurements with resolution of 10 -4 RIU [11]. The use of thin film coatings of refractive index higher than that of the cladding on both polished FBGs and TFBGS has been shown to allow the RI range over which the devices show their highest sensitivity to the tuned to lower values [10,12,13].…”
Section: Introductionmentioning
confidence: 99%